PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA SISWA KELAS 4 TEMA 1 TENTANG KEBERAGAMAN BUDAYA BANGSAKU - Amanda Pertiwi; Handayani Handayani; Yulita Dwi Lestari (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This research is a development research that aims to produce interactive multimedia products based on validity and practical unity.There search data were obtained using expert validation media, expert validation of learning, teacher questionnaires and student question naires, which were strengthened by documentation data. After the data is obtained, then a percentage of the data is searched using a predetermined formula to see the feasibility of the media being developed. The types of data used in this study are qualitative and quantitative data. Based on the results of this study, it is hoped that teachers will be able to develop technology-based media with the aim of creating learning fun and creating a new atmosphere in the classroom. It can be concluded that the development of Unity Based Interactive Multimedia for Bangsaku Cultural Diversity Sub-theme in Class IV Elementary Schools is included in the valid and practical category.